2021
DOI: 10.3390/brainsci11081020
|View full text |Cite
|
Sign up to set email alerts
|

Sarcotubular Myopathy Due to Novel TRIM32 Mutation in Association with Multiple Sclerosis

Abstract: Azerbaijani 28-year-old female showed weakness (MRC (Medical Research Council Scale for Muscle Strength) grade 4 in the proximal part of the upper and MRC grade 2–3 in the lower extremities), difficulty in stair lifting, positive symptom of Hoover’s rising, «waddling gait», decline deep reflexes symmetrical, lack of surface reflexes, positive Babinsky’s reflex on the right, urinary incontinence during sneezing, prolonged walking and exercise from puberty. Additional methods made it possible to identify minor v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…MMRI studies of the lower limbs were described in 49% (26/53) of the cases [our patient; ( 13 , 19 , 21 , 24 28 )]. Their images showed fibroadipose degeneration, with preferential affection of the posterior thigh compartment and selective sparing of specific muscles.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…MMRI studies of the lower limbs were described in 49% (26/53) of the cases [our patient; ( 13 , 19 , 21 , 24 28 )]. Their images showed fibroadipose degeneration, with preferential affection of the posterior thigh compartment and selective sparing of specific muscles.…”
Section: Resultsmentioning
confidence: 97%
“…We conducted a literature review of the clinical data related to 26 TRIM32 variants, carried biallelically (in either compound heterozygosis or homozygosis) by 53 LGMDR8 patients (included our proband). Clinical and instrumental findings extracted from the 20 extant studies are reported in Table 1 , and a visual summary of the LGMDR8 typical phenotype, based on the literature, is displayed in Figure 1A ( 7 , 11 , 13 , 15 30 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations